2021
DOI: 10.1186/s12891-021-04362-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of preoperative knee flexion contracture severity on short-term outcome of orthopedic surgery in ambulatory children with bilateral cerebral palsy

Abstract: Background Indications and cutoff value of deformities to determine surgical procedures for flexed knee gait are not clear. The aim was to determine the influence of none or mild, and moderate preoperative knee flexion contracture on the improvement of gait after orthopedic surgery in children with bilateral cerebral palsy (CP). Methods Inclusion criteria; bilateral CP, Gross Motor Function Classification System level I-III, and pre- and post opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…reduced step length), reduced metabolic efficiency, and deficient ankle power production (Abel & Damiano, 1996; Barber et al., 2017; Kurz, Arpin et al., 2012; Unnithan et al., 1996). Historically, the identification of the possible cause of an individual's gait impairments have centred on the musculoskeletal system, where it has been shown that many persons with CP often present bony torsional abnormalities, musculoskeletal contractures, muscular weakness, and alterations in the musculotendon architecture (Hanssen et al., 2021; Hegarty et al., 2020; Moreau et al., 2012; Pantzar‐Castilla et al., 2021). More recently, there has been a growing body of literature linking such gait impairments to alterations in the somatosensory and primary motor cortical activity that governs leg motor actions (George et al., 2021; Kurz, Wilson et al., 2014; Kurz, Heinrichs‐Graham et al., 2015; Kurz et al., 2020; Short et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…reduced step length), reduced metabolic efficiency, and deficient ankle power production (Abel & Damiano, 1996; Barber et al., 2017; Kurz, Arpin et al., 2012; Unnithan et al., 1996). Historically, the identification of the possible cause of an individual's gait impairments have centred on the musculoskeletal system, where it has been shown that many persons with CP often present bony torsional abnormalities, musculoskeletal contractures, muscular weakness, and alterations in the musculotendon architecture (Hanssen et al., 2021; Hegarty et al., 2020; Moreau et al., 2012; Pantzar‐Castilla et al., 2021). More recently, there has been a growing body of literature linking such gait impairments to alterations in the somatosensory and primary motor cortical activity that governs leg motor actions (George et al., 2021; Kurz, Wilson et al., 2014; Kurz, Heinrichs‐Graham et al., 2015; Kurz et al., 2020; Short et al., 2020).…”
Section: Introductionmentioning
confidence: 99%